PENGARUH PERBANDINGAN AGREGAT KERIKIL KRISIK (SEMEN 90%-ASP 10%) TERHADAP BERAT JENIS DAN VOLUME RONGGA BETON RINGAN NON PASIR - Ristiana Dyah Purwandari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2010)
This research shows how natural Krisik split-rice hull ash (RHA) can affect the density and the volume of dry concrete or no fines concrete composite to make concrete block. The analysis showed that the physical properties of RHA consisted of water content 6.38%, density 1.23³ gr/cm³, density of saturated dry surface 1.50 gr/cm³, apparent density 1.678 gr/cm³, water absorption capacity 21.27%, silica content (SiO2) 45.36% (amorf structure), and Alumina content (Al2O3) 3.12%. The physical properties of natural aggregate of Logawa river consisted of aggregate gradation of 1 field (525 natural krisik split), water content of natural krisik split 1.83%, specific bulk gravity 2.41%, specific bulk gravity of saturated dry surface 2.46 gr/cm³, specific apparent gravity 2.55gr/cm³, water absorption capacity 2.34%, and abrasion 33.4%. The ratio of concrete composite by natural krisik split was (cement 0.9 – RHA 0.1) varying from 4, 6. 8 and 10, reducing the specific density gravity of no fines concrete. One day-aged-no fines concrete showed equation of polynomial y=-0.0235x² + 0.9291x + 1.764, R² = 0.92; seven day-aged showed y=-0.0051x² + 0.0237x + 1.7505, R²= 0.92; and twenty eight-aged showed y=-0.0006 x² - 0.0411x + 2.0106, R²= 0.9827. But that composite increasing porous volume, the equation of ratio 10:1 showed y=2.3625x² - 9.805x + 207.21, R²= 0.9435 (one day-aged) and y=2.125x² - 8.05x + 199.6, R²= 0.9433 (twenty eight-aged). Key words: Rice Hull Ash, no fines concrete, natural krisik split, density, volume